2022
DOI: 10.1002/cac2.12254
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the interplay between long non‐coding RNAs and RNA‐binding proteins in cancer

Abstract: With the development of proteomics and epigenetics, a large number of RNAbinding proteins (RBPs) have been discovered in recent years, and the interaction between long non-coding RNAs (lncRNAs) and RBPs has also received increasing attention. It is extremely important to conduct in-depth research on the lncRNA-RBP interaction network, especially in the context of its role in the occurrence and development of cancer. Increasing evidence has demonstrated that lncRNA-RBP interactions play a vital role in cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(62 citation statements)
references
References 167 publications
1
45
0
Order By: Relevance
“…Interestingly, many researchers have recently found that the interaction between lncRNAs and RBPs plays a key role in tumor progression, 30 and most lncRNAs can interact with one or more RBPs. 31 Here, we first predicted the potential protein targets of DDX11-AS1 using the starBase v.2.0 website and then detected the proteins bound by DDX11-AS1 in glioma cells by CHIRP-MS.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, many researchers have recently found that the interaction between lncRNAs and RBPs plays a key role in tumor progression, 30 and most lncRNAs can interact with one or more RBPs. 31 Here, we first predicted the potential protein targets of DDX11-AS1 using the starBase v.2.0 website and then detected the proteins bound by DDX11-AS1 in glioma cells by CHIRP-MS.…”
Section: Discussionmentioning
confidence: 99%
“…ncRNAs can also interact with RNA-binding proteins, including m 6 A regulators, to regulate cancer cell phenotypes [ 101 ]. Zhu et al [ 102 ] reported that the lncRNA ARHGAP5-AS1 can recruit METTL3 to facilitate methylation of ARHGAP5 , which stabilizes ARHGAP5 in the cytoplasm.…”
Section: Biological Functions Of M 6 a Rna Modific...mentioning
confidence: 99%
“…17,18 LncRNAs mainly affect cancer progression by binding and interacting with RNAs, DNAs, and proteins. 19 The regulatory role of lncRNAs in tumors is also related to their localization, sequence, and secondary structure. 20 LncRNAs exert their regulatory roles in cells through a variety of mechanisms (Figure 1).…”
Section: Introductionmentioning
confidence: 99%